The problem of the formation and functioning of bilingualism in the family and society - Knol, M.; Assanova, D.; Tynbaeva, G. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
The article determines the conceptualization of “bilingualism” as a common phenomenon. The importance of this disputed point in the state of new multicultural sovereign state is emphasized. A minor overview of the scientific guidance is given in which the occasion of bilingualism is studied. The advantageous and opposite points of opinion of bilingualism researchers are considered, likewise as the contemporary attitude to this problem. Special importance is given to the formation of bilingualism in the family. Accomplishable variation of family bilingualism, age-related dilemma of bilinguals and ways to clear up them are considered. The article fix up with provision methodological recommendations for successfully overcoming difficulties in the upbringing of bilingual children. The article furthermore exposes the conceptualization of bilingualism and bilingual families, investigates the denotation and the role of bilingualism in the development of a kid in contemporary society, tells about the positive and negative sides of bilingualism in a child, the characteristic of the psychical organization of bilingual education.
Отбасы мен қоғамдағы екітілділіктің қалыптасуы мен қызмет ету мәселесі
Проблема формирования и функционирования двуязычия в семье и обществе
Keywords: bilingual families; bilingual children; bilingualism; natural bilingualism; bilingual; monolingual; multilingual; artificial bilingualism; multicultural society; multilingualism; language contacts